A comparison of genetic diversity between cultured and wild populations of marble goby from East Peninsular Malaysia - Ali @ Jaafar, Ruzainah; Mohd Nor, Siti Azizah; Othman, Ahmad Sofiman; Ismail, Patimah (2009)
This study reports on the assessment of genetic variation in partial mitochondrial DNA ND5 gene in six populations of wild and cultured populations of Oxyeleotris marmoratus (marble goby) collected from East Peninsular Malaysia. These were two cultured populations; HATCHERY1 (situated at Bachok) and HATCHERY2 (situated at Tanjung Demong); four wild populations – Tasik Bera (TBERA), Tasik Chini (TCHINI), Tasik Kenyir (TKENYIR) and Pulau Keladi (PKELADI). Twenty haplotypes were identified from 61 gene copies. Distribution of haplotypes showed that Tasik Kenyir had four population-unique haplotypes. Genetic population relationships were estimated by constructing NJ tree based on Jukes and Cantor parameter. The bookstrap value for NJ tree were calculated by 1000 replicates across loci. The unrooted dendrogram derived from Neighbour Joining (NJ) analysis generated three major clusters. This database demonstrate the utility of genetics tools in the evaluation of genetic diversity in the aquaculture industry.